Implementasi ARDUINO UNO R3 dan SENSOR DHT 11 Pada Perancangan Inkubator Penetas Telur Ayam Berbasis Mikrokontroler - Angga Sihasani; Dedy Hartama; Iin Parlina; Solikhun Solikhun; Sumarno Sumarno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Chicken farmers are currently having difficulty in determining the temperature to hatch chicken eggs because breeders only rely on the hen as the egg incubator. The DHT11 sensor is a sensor for reading the temperature and the ideal temperature for hatching chicken eggs is 37-39, the incubator automatically uses an incandescent lamp as its warmer and uses the DHT 11 sensor as a temperature and humidity incubator, and Ardunio Uno R3 as its microcontroller, incubator hatching chicken eggs work incandescent light bulbs will heat the room in an incubator and if it is already hot the DHT 11 sensor will read the incubator's temperature and humidity and will open through the LCD and if there is already a DHT11 sensor will be sent to the sensor relay to be sent incandescent lamps